By Land or by Sea: Paul’s Preferred Mode of Travel in the Acts of the Apostles - Reece, Steve (Tyndale bulletin, 2025)
By my calculations, the apostle Paul travelled over 12,000 kilometres by land and over 8,000 kilometres by sea just on the journeys that he made in the latter half of his life that happen to be recorded in the Acts of the Apostles. The modern reader cannot help but be astonished by these long distances. But what would have astonished an ancient Greek or Roman reader was not the sum total of the distances of Paul’s journeys but rather the ratio of land to sea travel. Most ancients who lived, like Paul, along the coast of the Eastern Mediterranean, ‘like frogs around a pond’ as Plato quips (_Phaed_. 109b), preferred to take the much easier, faster, and more efficient routes by sea, and the ratio of their land to sea travel would have been the reverse of Paul’s. Paul is depicted in the Acts of the Apostles as someone who shunned sea travel whenever possible and preferred to travel by foot rather than by ship in almost every instance in which this option was open to him.